Shifting the Beveridge Curve : What Affects Labor Market Matching? - Bova, Elva (IMF Working Papers; Working Paper ;, 2016)
This paper explores conditions and policies that could affect the matching between labor demand and supply. We identify shifts in the Beveridge curves for 12 OECD countries between 2000Q1 and 2013Q4 using three complementary methodologies and analyze the short-run determinants of these shifts by means of limited-dependent variable models. We find that labor force growth as well as employment protection legislation reduce the likelihood of an outward shift in the Beveridge curve,. Our findings also show that the matching process is more difficult the higher the share of employees with intermediate levels of education in the labor force and when long-term unemployment is more pronounced. Policies which could facilitate labor market matching include active labor market policies, such as incentives for start-up and job sharing programs. Passive labor market policies, such as unemployment benefits, as well as labor taxation render matching signficantly more difficult.